A cost-effective algae-based biosensor for water quality analysis: Development and testing in collaboration with peasant communities - Prudkin-Silva, C. (2021)
New anthropic potentially harmful compounds are released into the environment everyday. In this context, broad range bioassays have emerged providing economically viable and widely applicable alternatives due to their ability to detect the cumulative toxicity of mixtures of both known and unknown chemicals in a sample, thus allowing direct information about water quality. Here we present a low-cost, wide-range algae-based biosensor that is easy to assemble and operate by untrained users and provides direct readings. It was developed as a request of a peasant social movement organization to assess the toxicity of drinking water in rural communities affected by pesticide spraying. Two fresh water algae strains, Scenedesmus acutus and Pseudokirchneriella subcapitata, were immobilized in alginate beads and tested as bioindicators. After incubation with different pollutants for five days, naked eye analysis by several observers proved to be a successful method to survey algae’s growth and establish the detection limits. Best detection limits were 10 ppm for technical-grade acid glyphosate, 15 ppm for glyphosate-based formulation, 50 ppb for atrazine formulation, 7.5 ppm for copper and 250 ppb for chromium. Absorbance measurements upon algae resuspension validated these results. The developed device was successfully tested in participatory workshops conducted at rural communities. Children, adults and elders with no scientific training were able to build the sensor and interpret the results, thus evaluating the quality of rain and well water used in their communities.